2020
DOI: 10.1182/blood-2020-140457
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Power of Early, Sequential MRD Monitoring in Peripheral Blood and Bone Marrow in Patients with Mantle Cell Lymphoma Following Autologous Stem Cell Transplantation with or without Rituximab Maintenance; Final Results from the LyMa-MRD Project, Conducted on Behalf of the Lysa Group

Abstract: INTRODUCTION : Minimal residual disease (MRD) has emerged as an important predictor of clinical outcome in patients with mantle cell lymphoma (MCL). Its use in everyday clinical practice, however, remains uncertain since standardized MRD monitoring strategies and response criteria are not yet formally established. To address this question, we conducted the LyMa-MRD project as an ancillary biology study in a prospective phase III trial in MCL patients < 66 years of age (NCI NCT00921414; LyMa Trial; Le Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Interestingly, such a phenomenon was not reported by the MRD substudy of the LyMa trial, exploring rituximab as a post-ASCT maintenance treatment, probably suggesting a wider efficacy of this drug across all patient subgroups. 9 Finally, we were not able to identify clear correlations between LEN dose intensity and MRD kinetics, even though the limited number of patients provided with complete MRD and LEN dosage data (n = 45) hampered an accurate subgroup analysis of this phenomenon.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Interestingly, such a phenomenon was not reported by the MRD substudy of the LyMa trial, exploring rituximab as a post-ASCT maintenance treatment, probably suggesting a wider efficacy of this drug across all patient subgroups. 9 Finally, we were not able to identify clear correlations between LEN dose intensity and MRD kinetics, even though the limited number of patients provided with complete MRD and LEN dosage data (n = 45) hampered an accurate subgroup analysis of this phenomenon.…”
Section: Discussionmentioning
confidence: 86%
“… 6 Even if prospective and standardized, these RQ-PCR results are usually derived from merged tissues (mainly PB), and systematic comparison between BM and PB samples at different time points (as well as between IGH and BCL-1/IGH markers) is lacking. Moreover, MRD data from the LyMA phase 3 trial, which have so far been presented only in abstract form, 9 are focused on only 2 early time points (before and after ASCT) and are not conclusive regarding the prognostic value of MRD after ASCT, as very few MRD-positive results were recorded. On the other hand, the phase 2 Nordic trials described highly predictive MRD data from a selection of patients derived from 2 phase 2 studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the MRD analysis by Callanan et al. ( 33 ), RM provides longer PFS and OS regardless of MRD status pre- and post-ASCT in MCL pts who completed R-DHAP induction therapy. Sequential MRD monitoring during treatment offers strong potential for early clinical outcome prediction, as a surrogate clinical endpoint, and for MRD-guided, risk-adapted treatment in MCL.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of measurable residual disease (MRD) assessment has been well established in hematological neoplasms. Previously, several studies have shown its close correlation of MRD status with PFS and overall survival (OS) in MCL [9][10][11][12][13] . Its role in routine practice is yet to be de ned but will be in uenced by suitable modalities for real-world use 14 .…”
Section: Introductionmentioning
confidence: 99%